Intimate partner violence: Perceptions and attributions of male perpetrators - Cunha, Olga (2022)
here are many reasons to perpetrate intimate partner violence (IPV). This study analyzes the attributions and perceptions of Portuguese men who perpetrate IPV to understand their justifications for violence against their female partners. In-depth interviews were conducted with seven male perpetrators. Through thematic analysis, three main categories emerged: self, partner, and situational factors. Perpetrators identified self attributes as justifications to abuse, such as individual characteristics, emotional disturbances, and jealousy; partner attributes, such as partners’ characteristics and the use of violence against them; and situational factors, such as alcohol abuse and relational stressors. Perpetrators’ narratives evidenced a tendency to conceive violence as an unintentional and unplanned action, attributing violence to uncontrollable factors, and an attitude of non-accountability for their behaviors/actions. A deeper understanding of perpetrators’ perceptions and attributions for IPV will help to develop more effective intervention programs with offenders or to improve the existent ones, for example, in terms of dropout prevention, to reduce violence against women.